DETERMINAN BURUKNYA PERILAKU PENGELOLAAN SAMPAH RUMAH TANGGA MELALUI ANALISIS KORELASI KOEFISIEN KONTINGENSI DI DUSUN V DESA PATUMBAK KAMPUNG KECAMATAN PATUMBAK - Novrika Silalahi; Elmina Tampubolon (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Waste management is an effort to reduce and handle waste. Several factors cause the problem of waste to increase people's living standards which are not accompanied by harmony in knowledge about waste and also lack of participation or public attitude to maintain cleanliness and dispose of waste in its place. This is also influenced by the lack of Final Disposal Sites and the lack of government capacity in funding waste management locations. This study is aimed to determine the relationship between knowledge, attitudes, availability of trash bins, and the role of janitors with the behavior of housewives in managing household waste in Dusun V, Patumbak Kampung Village in 2021. This study used an analytical survey method with a cross sectional approach, which is carried out for 5 months from February to June 2021. The sample in this study were the heads of families in PatumbakKampung Village as many as 77 families who were selected by accidental sampling technique. The research instruments used questionnaires and interviews. Data analysis was carried out univariate and bivariate by using chi-square with a significance level of 95% (α = 0.05). The results showed that there was a relationship between knowledge (p = 0.002) and C = 0,292, attitude (p = 0.004) and C = 0,298, availability of trash bins (p = 0.001) and C = 0,348 and the role of janitor (p = 0.000) and C = 0,466. It is hoped that relevant agencies can be more active in supervising and providing strict sanctions against people who violate the applicable local regulations in order to create a deterrent effect, so that good waste management can be achieved.